El complejo de Campyloneurum angustifolium (Sw.) Fée (Polypodiaceae) en Costa Rica - Rojas Alvarado, Alexander Francisco (Lankesteriana: International Journal on Orchidology, 2015)
The Campyloneurum angustifolium complex in Costa Rica is analyzed. As a result, a new species is described (C. gracile A.Rojas), a comparative table and a key are included for the group.